Sosialisasi Penerapan Manajemen Logistik terhadap Produk Perishable dan Non Perishable - Iwan Prasetyo; Muhammad Navis Mirza; Rohmad Kafidzin (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
After assessing partner needs, it was found they lack knowledge in household logistics management for perishable and non-perishable items. Our goal is to educate the public on implementing household logistics for both types of products. To achieve this, we conducted a lecture and presentation of material regarding household logistics management, coupled with knowledge sharing sessions between partners and the service team. This method was chosen due to the low initial level of understanding among the partners. The results of this service initiative revealed the enthusiasm of partners, demonstrated through active discussions and a dynamic question-and-answer session with the service team. This interaction highlighted the partners' eagerness to learn and apply the concepts presented. It is hoped that through this educational effort, the community, as partners, will gain a better understanding of household logistics management and be able to apply it effectively in real-life scenarios. This will lead to improved management of both perishable and non-perishable items, reducing waste and ensuring more efficient use and storage of household goods.